2019
DOI: 10.1097/ta.0000000000002166
|View full text |Cite
|
Sign up to set email alerts
|

P-Selectin Is Critical for De Novo Pulmonary Arterial Thrombosis Following Blunt Thoracic Trauma

Abstract: BACKGROUND Thromboembolic events within the pulmonary arterial vasculature are a troublesome complication of severe blunt thoracic trauma. Mechanisms underlying these events are currently in question as pulmonary thromboembolic events in this particular trauma population tend to be diagnosed more rapidly, more frequently and without an associated systemic thrombosis. This study investigates the role of P-selectin in thrombus formation through the use of in vivo blocking antibodies. We hypothesize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
5
16
0
Order By: Relevance
“…8,9 In addition, we found that pretreatment with a P-selectin blocking antibody prevented pulmonary arterial thrombus formation after blunt thoracic trauma, confirming that pulmonary clot formation in the trauma population can arise via a unique mechanism of P-selectindependent in situ pulmonary thrombosis. 8 In this study, mice are treated with P-selectin blocking antibody after injury to investigate the clinical viability of this medication for the prevention of pulmonary thrombosis. In addition, viscoelastic testing is performed to investigate if P-selectin inhibition has a detrimental impact on normal hemostasis.…”
supporting
confidence: 56%
“…8,9 In addition, we found that pretreatment with a P-selectin blocking antibody prevented pulmonary arterial thrombus formation after blunt thoracic trauma, confirming that pulmonary clot formation in the trauma population can arise via a unique mechanism of P-selectindependent in situ pulmonary thrombosis. 8 In this study, mice are treated with P-selectin blocking antibody after injury to investigate the clinical viability of this medication for the prevention of pulmonary thrombosis. In addition, viscoelastic testing is performed to investigate if P-selectin inhibition has a detrimental impact on normal hemostasis.…”
supporting
confidence: 56%
“…Experimental studies have shown that chest trauma may induce focal inflammation and dysfunction in pulmonary vascular endothelial cells, eliciting in situ PAT ( Knudson et al, 2011 ; Brakenridge et al, 2013 ) ( Figure 1 ). For instance, in a mouse model of unilateral thoracic contusion, eccentric fibrin aggregates on and platelets adhere to the endothelial cells aligning inner surface of pulmonary arteries after chest trauma ( Brown et al, 2018 ), initiating in situ PAT ( Schutzman et al, 2018 ). Additionally, in situ PAT is associated with the aberrant pulmonary structures, such as pulmonary artery stump following pneumonectomy ( Kim et al, 2005 ; Kwek and Wittram, 2005 ), compensatory dilation and sheer stress at the proximal pulmonary artery caused by congenital cardiovascular defects and the resulting PH ( Celestin et al, 2015 ), and pulmonary tuberculosis-destoryed lungs ( Cha et al, 2015 ), as well as with the systemic predisposing conditions, including Behcet’s disease ( Yilmaz and Cimen, 2010 ), Eisenmenger’s syndrome ( Silversides et al, 2003 ; Broberg et al, 2007 ), sickle cell disease ( Mekontso Dessap et al, 2011 ), and other systemic diseases ( Porembskaya et al, 2020 ) ( Figure 1 ).…”
Section: The Risk Factors Of Pulmonary Thromboembolism Associated With Deep Vein Thrombosis and Of In Situ Pulmonary Amentioning
confidence: 99%
“…The released factors are rapidly transferred to the intraluminal surface and binds to P-selectin glycoprotein ligand 1 on platelets and leukocytes. Besides, the expression of P-selectin is also upregulated in platelet α granules ( López and Chen, 2009 ; Schutzman et al, 2018 ; Schutzman et al, 2019 ). P-selectin could further upregulate TF expression in leukocytes, particularly in monocytes, thus forming a positive feedback regulatory loop ( Figure 3 ).…”
Section: Common Pathogenic Mechanisms Underlying Thrombosismentioning
confidence: 99%
“…Although the number of microthrombi was increased in EBI after SAH and was further increased in ApoE-deficient mice, the mechanisms by which microthrombosis is affected after SAH remain elusive. P-selectin belongs to the adhesion glycoprotein family, which mediates leukocyte-endothelial cell and leukocyte-platelet adhesive interactions (27). It can be significantly upregulated and translocated to the surface of platelets and endothelial cells to promote vascular changes in many microcirculatory disturbance events.…”
Section: Discussionmentioning
confidence: 99%